Kant on the possibility of action from duty but not in accordance with duty - Urich, Georg (Trinity College (Dublin, Ireland). Philosophy Department, 2010)
The central theme of this study is a curious and controversial feature of Kant's account of acting from duty in the Groundwork:, his apparent omission of the possibility of action from duty but not in accordance with duty.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin.